(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the importance of learning a second foreign language for future philologists, emphasizing its role in broadening linguistic competence, enhancing cross-cultural understanding, and improving career opportunities. The ability to communicate in multiple languages is crucial for philologists, as it deepens their understanding of linguistic structures and cultural nuances. The study highlights the benefits of acquiring a second foreign language, such as cognitive development, improved employability, and expanded research potential. Special attention is given to the relevance of multilingualism in the context of globalization and the specific opportunities it offers to philology students in Uzbekistan.